2016
DOI: 10.1002/dev.21392
|View full text |Cite
|
Sign up to set email alerts
|

Extensive juvenile “babysitting” facilitates later adult maternal responsiveness, decreases anxiety, and increases dorsal raphe tryptophan hydroxylase‐2 expression in female laboratory rats

Abstract: Pregnancy and parturition can dramatically affect female neurobiology and behavior. This is especially true for laboratory-reared rodents, in part, because such rearing prevents a host of developmental experiences that females might undergo in nature, including juvenile alloparenting. We examined the effect of chronic exposure to pups during post-weaning juvenile life (days 22-36) on adult maternal responsiveness, anxiety-related behaviors, and dorsal raphe tryptophan hydroxylase-2 (TPH2) and serotonin transpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 124 publications
0
9
0
Order By: Relevance
“…We have no obvious explanation for this difference, but pre- and postpartum rats may differ in the abundance, affinity, or efficiency of DR SERT; the degree to which SERT is transported to the plasma membrane; or levels of extracellular serotonin that would affect competitive binding for reuptake. In fact, a study run in our laboratory contemporaneous to the present studies found that postpartum rats had ~30% more SERT in the DR compared to nulliparous virgin females [106].…”
Section: Discussionmentioning
confidence: 89%
“…We have no obvious explanation for this difference, but pre- and postpartum rats may differ in the abundance, affinity, or efficiency of DR SERT; the degree to which SERT is transported to the plasma membrane; or levels of extracellular serotonin that would affect competitive binding for reuptake. In fact, a study run in our laboratory contemporaneous to the present studies found that postpartum rats had ~30% more SERT in the DR compared to nulliparous virgin females [106].…”
Section: Discussionmentioning
confidence: 89%
“…The neurochemicals acting in these sites to modulate postpartum anxiety in postpartum laboratory rodents include norepinephrine, serotonin, and corticotropin releasing hormone [66,[68][69][70].…”
Section: ) Findings From Laboratory Rodent Modelsmentioning
confidence: 99%
“…On the other hand, extensive alloparental experience in virgin female rats for either 3 or 14 days reduces the expression of anxiety‐related behaviors as well as increases the expression of the rate‐limiting enzyme for serotonin synthesis in the 14 day condition (Harding and Lonstein, ). Similar results were seen in the alloparental African striped mouse ( Rhabdomys pumilio ), where alloparenting experience resulted in less anxiety‐related behavior in females (Pillay and Rymer, ).…”
Section: Reaction Of the Alloparentmentioning
confidence: 99%